All shook up : the shifting Soviet response to catastrophes, 1917-1991 - Raab, Nigel A., 1968- (McGill-Queen's University Press, 2017)
"All Shook Up examines major natural and man-made disasters in the Soviet Union. Specifically, it compares disasters in separate Soviet epochs, adding to our understanding of Soviet politics in discrete eras and of important transitions during periods of Soviet rule. The study analyses the 1927 earthquake in the Crimean peninsula shortly before Stalin came to power, the devastating earthquake in 1948 in Ashkhabad during high Stalinism, and the Tashkent earthquake in 1966, two years after Brezhnev took power, the Chernobyl explosion, and the Armenian earthquake in 1988. Based on archival research in Russia and Ukraine, All Shook Up shows the radical shifts in disaster policy from one leader to the next. While Soviet disasters have been studied from a scientific perspective, much less attention has been paid to the social, cultural and political dynamics that emerged in the aftermath of these tragedies. Gaining inspiration from disaster theorists such as Kenneth Hewitt and sociologists such as Erik Klinenberg, the book embeds each disaster within a specific context: changes brought about by disasters depended upon the specific cultural and political environment in which they occurred. While they did not affect everyone equally, disasters almost always evoked societal flux: in different forms, from active participation in recovery operations to the donation of money, citizens had an opportunity to act outside the regular parameters of Soviet life. Since disasters required the spontaneous mobilization of vast resources, they provide critical insights into the nature of the Soviet state. In these trying times, Soviet residents had an opportunity to craft their own worldview while the authoritarian Soviet state struggled to return a situation to normal. Moreover, this perspective reveals a dynamic rather than static Soviet Union in which individuals had ample room for improvisation."--